2005
DOI: 10.1002/jcp.20538
|View full text |Cite
|
Sign up to set email alerts
|

Normal and transforming functions of RUNX1: A perspective

Abstract: Converging studies from many investigators indicate that RUNX1 has a critical role in the correct maintenance of essential cellular functions during embryonic development and after birth. The discovery that this gene is also frequently mutated in human leukemia has increased the interest in the role that RUNX1 plays in both normal and transforming pathways. Here, we provide an overview of the many roles of RUNX1 in hematopoietic self-renewal and differentiation and summarize the information that is currently a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 146 publications
1
66
0
2
Order By: Relevance
“…The mutant transcript results in an in-frame deletion of 35 amino acids that disrupts part of the Runt homology domain and domains reported to bind the coactivators p300/CBP and corepressor Sin3A. 4 Owing to its limited resolution and the small size of the deletion, this aberration was not detected by whole genome SNP array on DNA derived from bone marrow of the proband, which did show a trisomy of chromosome 21. This trisomy has targeted the mutant allele as the deletion in the index patient was detected in two of the three copies of chromosome 21 (Figure 2b).…”
mentioning
confidence: 99%
“…The mutant transcript results in an in-frame deletion of 35 amino acids that disrupts part of the Runt homology domain and domains reported to bind the coactivators p300/CBP and corepressor Sin3A. 4 Owing to its limited resolution and the small size of the deletion, this aberration was not detected by whole genome SNP array on DNA derived from bone marrow of the proband, which did show a trisomy of chromosome 21. This trisomy has targeted the mutant allele as the deletion in the index patient was detected in two of the three copies of chromosome 21 (Figure 2b).…”
mentioning
confidence: 99%
“…AML1 has been reported to have a dual role in promoting cell cycle progression and differentiation, which may be dependent on the presence of different factors that are present (Mikhail et al, 2006). In T29 cells, we observed that AML1b inhibits the growth of these cells mediated possibly through upregulation Splice variant of AML1b confers loss of wild-type functions M Nanjundan et al of p21 levels, and further, inhibits the migratory potential of these cells.…”
Section: Discussionmentioning
confidence: 61%
“…Acute myeloid leukemia (AML) 1 belongs to a small family of transcriptional regulators whose members contain a DNA-binding runt homology domain (RHD) which have distinct tissue-specific expression and function (Mikhail et al, 2006). AML1 encodes the a-subunit of the transcription factor PEBP2/CBFb involved in the recognition of general transcription coregulators.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations